2009
DOI: 10.1007/s00223-009-9311-1
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Receptor-Like Factor 1 is Highly Expressed in Damaged Human Knee Osteoarthritic Cartilage and Involved in Osteoarthritis Downstream of TGF-β

Abstract: Osteoarthritis (OA) is the most prevalent joint disease and is characterized by pain and functional loss of the joint. However, the pathogenic mechanism of OA remains unclear, and no drug therapy for preventing its progress has been established. To identify genes related to the progress of OA, the gene expression profiles of paired intact and damaged cartilage obtained from OA patients undergoing joint substitution were compared using oligo microarrays. Using functional categorization combined with gene ontolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 41 publications
4
43
0
Order By: Relevance
“…There are only a few studies that address the issue of synovial or serum expression of cartilage-specific markers in patients with early-stage knee OA and limited synovitis in association with outcome and pain perception. In addition to our data about IGF-I, it has been shown that chondroitin 6-sulfate (C6S), chondroitin 4-sulfate (C4S), keratan sulfate (KS), and tenascin-C (TN-C), 19 cytokine receptor-like factor 1 (downstream of TGF-b), 47 or increased serum COMP (cartilage oligomeric matrix protein) levels 12 play a role as indicators or mediators in this stage of disease development. Because of its observational character, the study does not allow drawing any conclusions of how IGF-I is acting in detail, and it also remains unclear what molecular mechanisms are behind the observed association between synovial IGF-I levels and pain perception.…”
Section: Pain Perceptionmentioning
confidence: 86%
“…There are only a few studies that address the issue of synovial or serum expression of cartilage-specific markers in patients with early-stage knee OA and limited synovitis in association with outcome and pain perception. In addition to our data about IGF-I, it has been shown that chondroitin 6-sulfate (C6S), chondroitin 4-sulfate (C4S), keratan sulfate (KS), and tenascin-C (TN-C), 19 cytokine receptor-like factor 1 (downstream of TGF-b), 47 or increased serum COMP (cartilage oligomeric matrix protein) levels 12 play a role as indicators or mediators in this stage of disease development. Because of its observational character, the study does not allow drawing any conclusions of how IGF-I is acting in detail, and it also remains unclear what molecular mechanisms are behind the observed association between synovial IGF-I levels and pain perception.…”
Section: Pain Perceptionmentioning
confidence: 86%
“…Cartilage was classified macroscopically and collected separately from OA affected and preserved regions around the weight-bearing area of the joint (Figure S1). Classification was done based on predefined features of OA related damage as described previously [9], [10]: color/whiteness of the cartilage, surface integrity as determined by visible fibrillation/crack formation, and depth and hardness of the cartilage upon sampling with a scalpel. Care was taken to avoid contamination with bone or synovium.…”
Section: Methodsmentioning
confidence: 99%
“…In the degenerative joint condition of osteoarthritis, CRLF1 has been identified as a potential mediator of chondrocyte damage by 2 independent microarray studies of patient samples [55,56]. Expression in dysmorphic chondrocyte clusters [55] suggests a role that promotes cartilage degeneration in this common condition.…”
Section: Effects Of Clcf1 and Crlf1 Composite Cytokines On The Neuralmentioning
confidence: 98%
“…Expression in dysmorphic chondrocyte clusters [55] suggests a role that promotes cartilage degeneration in this common condition. CRLF1 levels in the chondrocyte cell line ATDC5 were promoted by transforming growth factor (TGF) b, and addition of CLCF1/CRLF1 to these CNTFR-expressing cells suppressed their expression of aggrecan and type II collagen (components of the healthy cartilage matrix) [55]. Crlf1 mRNA was rapidly upregulated in a mouse surgical model of osteoarthritis and did not depend on aggrecan degradation by ADAMTS5 [57].…”
Section: Effects Of Clcf1 and Crlf1 Composite Cytokines On The Neuralmentioning
confidence: 99%